Feminicídio como crime de ódio : uma análise a partir do caso Barbosa de Souza e outros vs. Brasil da Corte Interamericana de Direitos Humanos - Almeida, Gabrielle Souza O’ de (Universidade do Vale do Rio dos Sinos, 2023)
The present research aims to present feminicide as a form of hate crime targeting the female gender. The main objective is to understand to what extent feminicide can be identified as a hate crime within the Brazilian legal system, based on the interpretation of the Inter-American Court of Human Rights (IACHR), with emphasis on the case "Barbosa de Souza and others vs. Brazil.". The study seeks to understand the origins of feminicide, analyze its roots in male domination, and examine how it qualifies as a hate-motivated crime. Employing a qualitative approach, the research examines data on hate crimes and feminicides from the beginning of the COVID-19 pandemic to the present day, based on reports from the Brazilian Public Security Forum, the Institute of Applied Economic Research, and UN Women. The methodology used is monographic and comparative, investigating various categories of women to highlight the different forms of violations they face. The research reveals that feminicide has deep roots in the patriarchal structure of society. The witch hunts in Europe are examined as a historical precursor to hatred against women, highlighting how male domination perpetuates gender-based violence. The study also analyzes the case of Marcia Barbosa, demonstrating how intersectional factors of power, race, and class influence violence. It is concluded that feminist education, effective public policies, awareness, and comprehensive data collection are essential to combating feminicide as a hate crime.
Keywords: Feminicídio; Crimes de ódio; Violência de gênero; Direitos das mulheres; Caso Barbosa de Souza e outros vs. Brasil; Feminicide; Hate crimes; Gender-based violence; Women's rights; Barbosa de Souza and others vs. Brazil case; ACCNPQ::Ciências Sociais Aplicadas::Direito